2011
DOI: 10.1016/j.jacc.2011.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change in Coronary Artery Structure Assessed by Optical Coherence Tomography in Patients With Vasospastic Angina

Abstract: Objectives The aim of this study was to investigate the conformational change of arterial structure in the vasospastic lesion with optical coherence tomography. Background Coronary artery spasm plays an important role in the pathogenesis of ischemic heart diseases. The conformational change of each arterial layer during vasospasm has not been studied in detail. Methods We assessed 19 coronary arteries (10 spasm and 9 nonspasm lesions) with optical coherence tomography during the provocation test for corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 19 publications
2
44
0
6
Order By: Relevance
“…15,16 Moreover, intracoronary imaging by optical coherence tomography has greater resolution and may provide further insight into the characteristics of vasospastic segments, such as increased basal smooth muscle tone in the media. 17 Studies using Holter monitoring or exercise testing have described a diurnal pattern with many episodes of coronary artery vasospasm occurring in the early morning, as in our patient's case. 18,19 Although not necessary in this case, provocative testing using intravenous or intracoronary injection of methylergonovine or ergonovine or intracoronary injection of acetylcholine can be useful in diagnosing coronary artery vasospasm in the patients with normal-appearing coronary arteries on angiography but a clinical presentation concerning for vasospasm; such provocative testing holds a class IIB recommendation from the American Heart Association/American College of Cardiology and a class IIA recommendation by the European Society of Cardiology for this indication.…”
Section: February 23 2016supporting
confidence: 55%
“…15,16 Moreover, intracoronary imaging by optical coherence tomography has greater resolution and may provide further insight into the characteristics of vasospastic segments, such as increased basal smooth muscle tone in the media. 17 Studies using Holter monitoring or exercise testing have described a diurnal pattern with many episodes of coronary artery vasospasm occurring in the early morning, as in our patient's case. 18,19 Although not necessary in this case, provocative testing using intravenous or intracoronary injection of methylergonovine or ergonovine or intracoronary injection of acetylcholine can be useful in diagnosing coronary artery vasospasm in the patients with normal-appearing coronary arteries on angiography but a clinical presentation concerning for vasospasm; such provocative testing holds a class IIB recommendation from the American Heart Association/American College of Cardiology and a class IIA recommendation by the European Society of Cardiology for this indication.…”
Section: February 23 2016supporting
confidence: 55%
“…optyczna koherentna tomografia) mogą się niekiedy okazać przydatne w identyfikacji zmian odpowiedzialnych za niedokrwienie lub patologii leżą-cych u ich podstaw, tj. pogrubienie warstwy środkowej tętnicy spowodowane jej nieprawidłowym obkurczeniem w skurczu tętnicy wieńcowej lub powierzchowne nadżerki w obrębie pokrywy włóknistej w zmianie miażdżycowej niepowodującej istotnego zwężenia [318][319][320].…”
Section: Identyfikacja Zmiany Odpowiedzialnej Za Niedokrwienieunclassified
“…These reports indicated that intracoronary erosion and thrombus formation may occur within spastic segments. Using OCT, Tanaka et al [8] demonstrated initial gathering, characterized by folding or gathering of the intima, at spastic segments during spasm. Therefore, coronary spasms may lead to hypercontraction and extension of the intima, which results in coronary erosion formation.…”
Section: Discussionmentioning
confidence: 99%